Impact of a new benchmark on the OTC market: evidence from Brazil - Cereda, Fábio Saia (2019)
This paper can be divided in two main parts. First, we analyze the effects of the publication of a new benchmark on the Brazilian stock lending market. In the second part, we use the findings provided by the first analysis to create an instrument to assess the relation between short-selling and two characteristics of the spot market: price efficiency and stock liquidity. The study is based on a unique data set of all the loan contracts for a 60-day window around the introduction of the benchmark, containing the information of 162,195 deals of 279 tickers. We present three main findings. First, the publication of the new benchmark caused an overall reduction in average loan fees, and a narrowing of loan and brokerage fee dispersion. Second, the impact on loan fees was higher for tickers with a history of high volatility, high average loan fee and low average number of borrowers per day. Third, short-selling constraints - measured by the exogenous variation of loan fees - are associated with lower price efficiency, and an inconclusive result for market liquidity